ظاهرة التناص من منظور علم لغة النص: آلية التفصيل بعد الإجمال في القرآن الكريم نموذجاً: The Phenomenon of Intertextuality from the Perspective of Text Linguistics: The Mechanism of “Detail after Summarization” in the Quran as a Model - bin Zabidin, Mohd Azizul Rahman; Ahmad Eldesoky, Ebrahim Mohammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يهدف هذا البحث إلى دراسة ظاهرة التناص من منظور علم لغة النص، مع التركيز على آلية "التفصيل بعد الإجمال" بوصفها أداة رئيسية في تحقيق الاتساق النصي. وتبرز مشكلة البحث في غياب الدراسات التي تربط بين التناص وآلية التفصيل بعد الإجمال ضمن النصوص الدينية، لا سيما القرآن الكريم، مما يستدعي إجراء تحليل عميق لهذه العلاقة. ومن هذا المنطلق، يسعى البحث إلى توضيح العلاقة بين التناص وآلية التفصيل بعد الإجمال وبيان دور هذه الآلية في تحقيق الاتساق النصي في القرآن الكريم. وجد الباحثان المنهج الوصفي التحليلي منهجا مناسبا لدراسة الموضوع دراسة نصية؛ لأنه يحتاج إلى دراسة وصفية لتوضيح مفهوم التناص وآليته التفصيل بعد الإجمال، أما المنهج التحليلي فيساعد الباحثين في دراستهما التحليلية لظاهرة التناص بآلية التفصيل بعد الإجمال في القرآن الكريم. وقد توصل البحث إلى عدة نتائج، من أبرزها أن آلية التفصيل بعد الإجمال تسهم بشكل كبير في تحقيق الاتساق النصي، كما أن توظيفها في النصوص القرآنية يعزز وضوح المعنى ويساعد في تفسير النصوص الدينية بفعالية. يقدم البحث إضافة نوعية عبر دمج مفهوم التناص مع إحدى آلياته التطبيقية، مما يسهم في تطوير الدراسات النصية. يوصي البحث بتوسيع نطاق الدراسات المستقبلية لتشمل نصوصًا أدبية ودينية متنوعة، مع استخدام مناهج تحليلية متعددة لتعميق الفهم المتعدد الأبعاد لظاهرة التناص. ABSTRACT This study aims to examine the phenomenon of intertextuality from the perspective of text linguistics, with a particular focus on the mechanism of "detail after summarization" as a key tool in achieving textual cohesion. The research problem lies in the absence of studies that establish a connection between intertextuality and the mechanism of detail after summarization within religious texts, particularly the Quran, necessitating an in-depth analysis of this relationship. Accordingly, this study seeks to elucidate the relationship between intertextuality and the mechanism of detail after summarization, highlighting its role in enhancing textual cohesion in the Quran. The researchers adopted the descriptive-analytical method as the most suitable approach for a textual study of this nature. The descriptive aspect helps clarify the concept of intertextuality and its mechanism, while the analytical method enables an in-depth examination of intertextuality through the lens of detail after summarization in Quranic texts. The study reached several key findings, most notably that the mechanism of detail after summarization significantly contributes to textual cohesion. Moreover, its application in Quranic discourse enhances clarity of meaning and facilitates a more effective interpretation of religious texts. This study provides a valuable contribution by integrating intertextuality with one of its practical mechanisms, thereby advancing research in text linguistics. Finally, the study recommends broadening the scope of future research to include a diverse range of literary and religious texts while employing multiple analytical methodologies to deepen the multidimensional understanding of intertextuality.